2019
DOI: 10.1039/c9tc01301f
|View full text |Cite
|
Sign up to set email alerts
|

Directed polymorphism and mechanofluorochromism of conjugated materials through weak non-covalent control

Abstract: Understanding and manipulating crystal polymorphism can provide novel strategies for materials discovery in organic optoelectronics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 67 publications
(90 reference statements)
0
22
0
Order By: Relevance
“…We further showed how competitive interactions in PE structures can tailor both their optical properties in solids and their MFC response. A series of ester-terminated PEs exhibited polymorphism that strongly depended on alkyl chain length, where the prevalence for polymorph appearance could be modulated via competition between interactions of alkyl chains and ArF–ArH stacking . More surprisingly, we found that twisting can depend on the regiochemistry of fluorine substitution of the ArF rings, with solids of side chain regioisomers exhibiting divergent optical properties.…”
Section: Interactions Of Aromatic Rings: Tunable Stacking and Dynamic...mentioning
confidence: 73%
See 1 more Smart Citation
“…We further showed how competitive interactions in PE structures can tailor both their optical properties in solids and their MFC response. A series of ester-terminated PEs exhibited polymorphism that strongly depended on alkyl chain length, where the prevalence for polymorph appearance could be modulated via competition between interactions of alkyl chains and ArF–ArH stacking . More surprisingly, we found that twisting can depend on the regiochemistry of fluorine substitution of the ArF rings, with solids of side chain regioisomers exhibiting divergent optical properties.…”
Section: Interactions Of Aromatic Rings: Tunable Stacking and Dynamic...mentioning
confidence: 73%
“…A series of ester-terminated PEs exhibited polymorphism that strongly depended on alkyl chain length, where the prevalence for polymorph appearance could be modulated via competition between interactions of alkyl chains and ArF−ArH stacking. 203 More surprisingly, we found that twisting can depend on the regiochemistry of fluorine substitution of the ArF rings, with solids of side chain regioisomers exhibiting divergent optical properties. While an anisyl-terminated PE with 2,4,6-trifluorinated side chains exhibited blue fluorescent films and a twisted, nonaggregated crystal structure, a 2,3,6-trifluorinated analog exhibited yellow emission in solidsa fluorescence shift of 136 nmwith a representative crystal structure showing coplanar and aggregated PEs.…”
Section: ■ Halogen-bonding Interactions: 2dmentioning
confidence: 75%
“…As they are not coupled to the conjugated system, incorporating directional interactions into side chains enables structural control that is orthogonal to the function of the main chain and broadly applicable for many classes of main chain structures. Analogous to the design in Chart , our group’s previous work has demonstrated side chain engineering for guiding optical and responsive properties in phenylene-ethynylenes (PEs) via electron-poor fluoroarene pendants that cofacially stack with arenes in the PE chromophore (ArF–ArH interactions). This robust aromatic stacking interaction is useful in a variety of contexts to direct molecular packing. To accommodate these interactions, the PE linkages twist out of coplanarity by at least 55°, reducing conjugation. In addition, these ArF–ArH interactions insulate the PE chromophores from each other by blocking regions of overlap that are otherwise required for through-space coupling.…”
Section: Introductionmentioning
confidence: 99%
“…82 Little was known about such relationship before this study. 83 Specifically, derivatives 35b and 35c crystalized as plate-like crystals and exhibited MCL behaviors. On the other hand, the emission color of needle-like crystals of 35dg remained unchanged after grinding.…”
Section: Strategies To Controlling the MCL Propertiesmentioning
confidence: 99%